Wide Line Surface‐Enhanced Raman Scattering Mapping. Issue 6 (22nd April 2020) - Ilchenko, Oleksii; Slipets, Roman; Rindzevicius, Tomas; Durucan, Onur; Morelli, Lidia; Schmidt, Michael S.; Wu, Kaiyu; Boisen, Anja
Abstract: Surface‐enhanced Raman spectroscopy (SERS)‐based molecular detection at extremely low concentrations often relies on mapping of a SERS substrate. This yields a large number (>1000) of SERS spectra that can improve the limit of detection; however, the signal collection time is a major constraint. In this work, a wide line (WL) laser focusing technique aimed at fast mapping of SERS substrates is presented. The WL technique enables acquisition of thousands of SERS spectra in a few seconds without missing any of the electromagnetic "hot spots" in the illuminated area. In addition, the SERS signal averaging across the line in the WL mode displays extremely high signal‐to‐noise ratios. The advantages of the WL technique for SERS‐based sensing are verified using different analyte molecules, that is, p‐coumaric acid and melamine. Results show that the limit of detection can be improved by one order of magnitude compared to results obtained using a commercial Raman microscope. Abstract : Wide line laser focusing technology for surface‐enhanced Raman scattering (SERS) substrate mapping has been developed. The designed microscope enables collecting thousands of spectra in a few seconds without missing any "hot spots" during mapping of the SERS substrate. The SERS signal averaging across the line in the wide line mode displays extremely high signal‐to‐noise ratios.